(untitled) (Desarrollo, Estado y Espacio, 2023)
The article proposes a look at the island territory in two territorial configurations of the Lower Paraná Delta from the registration of landscape signs and the modes of habitation present in the narratives of its residents. The underlying research is aimed at answering the following questions: what circuits link the islands and their inhabitants? And with the territory-continent? What rules organize the island landscape? When and how does "the common" come into play? What experiences of public-private articulation are developed? How does the State act in the island territory? This is a qualitative research based on semi-structured interviews, life stories and analysis of visual sources, especially from personal photographic albums. In the first instance, we introduce the conceptual discussion on the borders and new frontiers between the urban, the rural and the natural in the recent reflection on the so-called water territories. We will focus on the problem of the constitution of common spaces and their transformations over time based on biographical accounts. We then present some characteristics of the two chosen case studies, their settlement processes and a selection of public interventions that contributed to their current configuration. Next, we propose three readings on the forging of these water territories. One about the origin, a second which focuses on the most recent process of occupation of the island where the logic of the market appears as a "predator" of the authentic island space against the backdrop of an absent State. Finally, using visual sources, we talk about the affective landscape, a record that shows the transformations of the landscape and common spaces from the perspective of the islanders’ memory.